Green Chemistry in Government and Industry - Benvenuto, Mark Anthony; Plaumann, Heinz (Green Chemical Processing ;, 2020)
The 5th volume of Green Chemical Processing considers sustainable chemistry in the context of governmental and corporate interests, explaining how "red tape" can help or hinder the "greening" of industry processes. The American Chemical Society's 12 Principles of Green Chemistry are woven throughout this text as well as the series to which this book belongs.